Implementation of a MIPS32 system based learning of wireless technologies - Oliden Martínez, José F. (2014)
Currently teaching related electronic technologies requires students to bring increasingly complex technologies such as wireless communications systems. To achieve this approach we have implemented a prototype system hardware that includes a MIPS32 processor architecture and technologies embedded wireless modules Wi-Fi, Bluetooth, GSM / GPRS, ZigBee and GPS. Whose main function is to monitor the synchronized operation of the wireless communication between modules. On the other hand it has developed an application Graphical User Interface or GUI- programmed QT Creator v2.3 open source platform used to enter configuration commands or receive data or wireless modules. The method of approach that has the student with the system through a laboratory manual is made whose content has an active learning methodology comprising motivation, acquisition, transfer and evaluation of knowledge.